The proceedings or preliminary inquiries from the perspective of the principle of procedural legality - Zavaleta Verde, Arturo Alexander Roberth (2023)
This article analyzes whether the Public Ministry, from the perspective of the principle of procedural legality, is empowered to carry out actions or inquiries prior to the classification of criminal news; For this purpose, first the role played by the holder of the exercise of criminal action in the investigation stage is theorized; then, the position established by the Supreme Court and the opinion of the doctrinaires of criminal procedural law are presented; concluding, that the previous actions are regulated in our legislation, therefore they are not contrary to the principle of procedural legality.